2015
DOI: 10.1016/j.juro.2015.05.086
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological Validation of the Surface-Intermediate-Base Margin Score for Standardized Reporting of Resection Technique during Nephron Sparing Surgery

Abstract: Purpose: The surface-intermediate-base margin score is a novel standardized reporting system of resection techniques during nephron sparing surgery. We validated the surgeon assessed surface-intermediate-base score with microscopic histopathological assessment of partial nephrectomy specimens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…5 The authors attempted to validate the scoring system in a follow up analysis. 29 The SIB scoring system provides is predicated on the surgeon's ability to accurately assess the presence or absence of residual parenchyma around various sections of the removed renal tumor. The i-Cap scoring system, determined by histopathological analysis, may function as an ideal complement to aforementioned SIB system in that it may provide a checks and balances to the surgeon's assessment on a microscopic level.…”
Section: Discussionmentioning
confidence: 99%
“…5 The authors attempted to validate the scoring system in a follow up analysis. 29 The SIB scoring system provides is predicated on the surgeon's ability to accurately assess the presence or absence of residual parenchyma around various sections of the removed renal tumor. The i-Cap scoring system, determined by histopathological analysis, may function as an ideal complement to aforementioned SIB system in that it may provide a checks and balances to the surgeon's assessment on a microscopic level.…”
Section: Discussionmentioning
confidence: 99%
“…We prefer the enucleo‐resection technique, dissecting along the renal pyramids , even if results using enucleation around the pseudo‐capsule of the tumour have shown equivalent oncological outcomes . Recently, the Surface‐Intermediate‐Base Margin score has been introduced to standardize reporting of resection techniques during nephron‐sparing surgery . This will be very helpful for comparing the different resection techniques prospectively.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the shorter WIT, postoperative renal function did not differ between the groups. The impact of ETHOS on surgeons' physical ergonomics has been studied extensively previously, showing a significant reduction of the mean complaint score from 31.6 (20-40) to 13.9 (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24), mainly as a result of less shoulder stiffness, arm pain, hand pain, wrist stiffness, back and leg pain [12,13].…”
Section: Matched Pair Analysis: Impact Of Ergonomic Chairmentioning
confidence: 99%
“…While, the actual postoperative surgical result (resection technique) could be classified according to a careful analysis of the specimen after surgery. In this regard, the Surface-Intermediate-Base (SIB) Margin score was recently proposed to provide the literature with a standardized reporting system of resection techniques during NSS and we recently validated the model from the histopathological perspective [1,2]. We have shown that the visual definitions of resection techniques used to calculate the score do significantly mirror histopathological analysis to quantify and report the thickness of healthy renal margin resected by the surgeon.…”
Section: Future Perspectivesmentioning
confidence: 99%